2019
DOI: 10.3904/kjim.2017.058
|View full text |Cite
|
Sign up to set email alerts
|

Circulating renalase predicts all-cause mortality and renal outcomes in patients with advanced chronic kidney disease

Abstract: Background/Aims Patients with chronic kidney disease (CKD) have been found to show markedly increased rates of end-stage renal disease, major adverse cardiovascular and cerebrovascular events (MACCEs), and mortality. Therefore, new biomarkers are required for the early detection of such clinical outcomes in patients with CKD. We aimed to determine whether the level of circulating renalase was associated with CKD progression, MACCEs, and all-cause mortality, using data from a prospective randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…Furthermore, we also observed that a low post-PCI serum renalase level could predict a lower risk for the composite endpoint including a first episode of myocardial infarction, stroke, and all-cause mortality. In line with our longitudinal follow-up findings for patients with established CAD, high baseline serum renalase levels were found to predict a high risk of all-cause mortality in patients with CKD in a prospective observational study [ 21 ], although a low plasma renalase concentration was observed in patients with CAD in a cross-sectional study [ 29 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, we also observed that a low post-PCI serum renalase level could predict a lower risk for the composite endpoint including a first episode of myocardial infarction, stroke, and all-cause mortality. In line with our longitudinal follow-up findings for patients with established CAD, high baseline serum renalase levels were found to predict a high risk of all-cause mortality in patients with CKD in a prospective observational study [ 21 ], although a low plasma renalase concentration was observed in patients with CAD in a cross-sectional study [ 29 ].…”
Section: Discussionsupporting
confidence: 79%
“…Renalase produced by the kidney is a flavin-adenine-dinucleotide-dependent amine oxidase that metabolizes catecholamines [ 20 ]. The circulating concentration of renalase is reportedly increased in patients with chronic kidney disease (CKD) and might predict mortality in this population [ 21 ]. CAD is prevalent in patients with CKD, and the pathogenesis between CAD and CKD is complex [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The elevation in serum renalase has been also repeatedly associated with heart and circulatory dysfunctions, very common in the CKD, since heart seems to be another very important source of RNLS. Low concentration of renalase is considered as one of the predictive factors of coronary artery disease (CAD) [8,12,22], and an increase in serum renalase is associated with significantly greater hazards of all-cause mortality and adverse renal outcomes [23]. In our study, the presence of hypertension or any of cardiovascular disease had no impact on renalase concentration.…”
Section: Discussionmentioning
confidence: 57%
“…Low concentration of renalase is considered as one of the predictive factors of coronary artery disease (CAD) (8,12,23), and an increase in serum renalase is associated with significantly greater hazards of all-cause mortality and adverse renal outcomes (24). In our study, the presence of hypertension or any of cardiovascular disease had no impact on renalase concentration.…”
Section: Discussionmentioning
confidence: 57%